The online journalism handbook : skills to survive and thrive in the digital age - Bradshaw, Paul, ....-; Rohumaa, Liisa, ....- (Harlow : Pearson Education, 2011)
How do we practice journalism in a digital world, in which the old 'rules' no longer apply? This text offers comprehensive, instructive coverage of the techniques and secrets of being a successful online journalist, both from a theoretical and practical point of view. Reflecting the vitality of the web, it will inspire aspiring journalists to acquire new skills and make sense of a transforming industry.
Keywords: Journalistiek en internet